STRENGTH ANALYSIS OF STEEL ROPE ON FREIGHT ELEVATOR WITH A HOIST LIFTING CAPACITY OF 3 TONS - Risdiyan, Asep; Haftirman, Haftirman; Arwati, I Gusti Ayu (Universitas Mercu Buana, 2024)
Steel rope has advantages over chains, but also has disadvantages. The advantage is that it is resistant to shock loads, if it breaks it shows a brittle sign on one of the wires (Houda Mouradi, 2018). The drawbacks are that they are not resistant to corrosion, are difficult to bend, can stretch or elongate, and tend to rotate (Aginaparru, 2018). In this study the analysis carried out was the process for the Salt Spray test to determine the effect of the corrosion rate on steel rope and the tensile test process aimed at determining the phase transformation, plasticity, creep, fatigue, to the fatigue point, as well as metallographic tests for changes in the properties mechanic. Loss or loss of weight on steel rope type 6 x Fi (29), diameter 13 from the salt spray test process, increased the corrosion rate from 0.21 mpy to 0.23 mpy. The greater the tensile force, the greater the tensile stress that occurs. And the greater the tensile force, the greater the elastic modulus that occurs from the elastic limit to the fatigue limit due to the magnitude of the tensile force that exceeds the limit. In metallographic testing using the ASTM 317 / ASTM E 407 method, it can be concluded that the steel rope has a modulus of elasticity, visible crack lines in the steel rope structure indicating that the steel rope has undergone an elastic process to the fatigue limit or fracture limit. Keywords: Salt Spray, wire, creep, fatigue